2018
DOI: 10.1097/md.0000000000013040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microecological preparation supplementation on woman with polycystic ovary syndrome

Abstract: Background:Polycystic ovary syndrome (PCOS) is the most common endocrine disorder among women of reproductive age. PCOS not only affects female fertility, but is also associated with a variety of metabolic diseases, such as type 2 diabetes. Microecological preparations include probiotics, prebiotics, and synbiotics, and a number of studies have shown its advantages in reducing cardiovascular and cerebrovascular diseases in patients with PCOS, however, no meta-analysis has been performed to confirm that. Herein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…No adverse effects of probiotic supplementation were observed [118]. A meta-analysis by Zhang [119] showed that probiotics can reduce total cholesterol, triglycerides and low-density lipoprotein cholesterol levels, in-crease high-density lipoprotein cholesterol and consequently reduce the long-term cardiovascular risk of PCOS patients. But they also pointed out the limitations of current studies on probiotics supplementation, including the fact that the probiotics used in each study varied widely and no standard dosages were used, points which will need to be addressed in future studies.…”
Section: Probiotic Therapymentioning
confidence: 99%
“…No adverse effects of probiotic supplementation were observed [118]. A meta-analysis by Zhang [119] showed that probiotics can reduce total cholesterol, triglycerides and low-density lipoprotein cholesterol levels, in-crease high-density lipoprotein cholesterol and consequently reduce the long-term cardiovascular risk of PCOS patients. But they also pointed out the limitations of current studies on probiotics supplementation, including the fact that the probiotics used in each study varied widely and no standard dosages were used, points which will need to be addressed in future studies.…”
Section: Probiotic Therapymentioning
confidence: 99%
“…Microecological preparations, such as probiotics, prebiotics, and synbiotics, comprise one of the safe approaches to improve the composition of gut microbiota in humans [11] that positively regulate inflammatory bowel disease [12], infection by Clostridium difficile [13], immune responses [14], and diabetes [15]. Probiotics reduce body weight, BMI, and fat percentage in overweight or obese individuals [16].…”
Section: Introductionmentioning
confidence: 99%